19’TH CENTURY ISLAMIC RENEWAL - Jahrani, Jahrani; Putra, Rehan Ariansyah; Tri setya, Arizal Hangga (SERUMPUN : Journal of Education, Politic, and Social Humaniora, 2023)
This paper is about Islamic renewal in the 19th century that emerged as a response to the challenges of modernization faced by the Islamic world at that time. This renewal movement aims to restore the glory of Islam through renewal of religious thought and practice that is more in line with the demands of the times. This renewal movement was spearheaded by intellectual figures such as Jamaluddin al-afghani, Muhammad Abduh, Sayed Ahmad Khan, Muhammad Iqbal, and Rashid Ridha. Islamic thought and renewal movements in the 19th century had several important contributions in facing the challenges of modernization, namely bringing new thoughts that were more open and inclusive of socio-political and cultural changes in the Islamic world. However, this movement faced major challenges, especially in overcoming resistance and conservatism among traditional religious leaders. Therefore, it requires the support and active participation of the Islamic community to encourage the process of renewal and more open and inclusive thinking.